Effect of fractionated antigens of Mycobacterium bovis AN5 on blood mononuclear cells of cattle - JOARDAR, S N; RAM, G C (The Indian Journal of Animal Sciences, 2012)
Potentiation of mononuclear immune-effector cells against mycobacteria is very much needed to prevent bovine tuberculosis. Immunopotentiating activities of various antigenic components of mycobacteria were studied previously. But knowledge regarding Mycobacterium bovis specific antigenic molecules is meagre that might be used as inducers of mononuclear immune-effector cells. With the aim of characterizing immunogenic components of M. bovis, gel filtration and anion-exchange chromatography were performed to fractionate antigens in the present study. Nitrite production by blood mononuclear cells of sensitized calves upon stimulation with fractionated antigens of M. bovis AN5 was estimated. The lymphoproliferative activity was also assessed using the similar set of antigens. One of the M. bovis specific fractionated antigens was potent inducer of both lymphoproliferation and nitrite production by mononuclear cells in vitro, than the crude antigen preparation.